Results of Faecal Sludge Analyses in Kampala, Uganda - Schoebitz, L.; Bischoff, F.; Ddiba, D.; Okello, F.; Nakazibwe, R.; Niwagaba, C.B.; Lohri, C.R. (eawag Aquatic research, 2014)
As part of a collaborative research project conducted by Eawag/Sandec and Makerere University, 180 faecal sludge samples were collected and analyzed in Kampala, Uganda from November 2013 to April 2014. Presented in this report are quantitative and qualitative results, alongside pictures of 76 samples taken in the laboratory and from the onsite location where samples were collected. This information is expected to be helpful to further understand the characteristics and variability of different sources of faecal sludge, and also to develop qualitative knowledge regarding the visual appearance of faecal sludge with different characteristics. Some of this data has been used in the preparation of a journal article (Schoebitz et al. submitted). We are also sharing it here, because to our knowledge it is the first time that such extensive knowledge of faecal sludge characteristics has been made openly available in one document. By the end of the sampling campaign, the research assistant who processed all of these samples was able to reliably predict the range of COD in the sample based on a qualitative visual analysis of foam, color and viscosity (but on odor). We are hoping that some of this laboratory experience can be transferred by sharing these results. Potentially this could lead to inexpensive field methods for estimated characterization of faecal sludge in the field or at treatment plant inlets in low-income countries. Viscosity and odor can be qualitative predictors of COD and total solids with long-term experience, and to a certain extent color.
Keywords: Faecal sludge analyses